The Influence of Brand Awareness Customer Value and Customer Satisfaction on Interest in Renting Daya Cipta Sejati (Dcs) Cars in Cinere Depok - Bimo Putro Karsodimedjo; Resti Hardini; Kumba Digdowiseiso (Jurnal Syntax Admiration, 2023)
This study aims to analyze the influence of Brand Awareness, Customer Value and Customer Satisfaction on Renting Interests at Daya Cipta Sejati (DCS) car rentals in Cinere Depok. The research method used is a quantitative method and uses multiple linear regression analysis with processing using Statistical Product and Service Solutions (SPSS) version 23 with data collection methods through questionnaires to 100 respondents using the Daya Cipta Sejati (DCS) car rental. The results of this study indicate that the variable Brand Awareness has no positive and significant effect on Renting Interests for Daya Cipta Sehati (DCS) car rentals. Customer Value has a positive and significant effect on Renting Interests for Daya Cipta Sehati (DCS) car rentals., and Customer Satisfaction has a positive and significant effect on Re-Lease Interests for Daya Cipta Sehati (DCS) car rentals